Functional Analysis of OsCIPK17 in Rice Grain Filling - Gao, Cong; Zhu, Xiuru; Lu, Shuai; Xu, Jingbiao; Zhou, Rong; Lv, Jianying; Chen, Yaoyu; Cao, Yunying (Frontiers in Plant Science, 2022)
We used mutant cipk17 and Nipponbare in field experiments to analyze agronomic traits, photosynthetic parameters, transcriptome, and gene expression. The results demonstrated cytoplasmic localization of OsCIPK17, while GUS allogeneic tissue-staining and quantitative analysis showed the gene was expressed in many organs, including flower buds; furthermore, it was involved in root, stem, and leaf growth. Compared to Nipponbare plants, grain filling rate and final grain weight decreased in plants of the knockout mutant owing to a delay in attainment of maximum grain filling rate. Photosystem II efficiency was also reduced. Enrichment analysis showed that the functions of differentially expressed genes focused on nucleoside-, nucleotide-, and lipid-binding, as well as hydrolase, transferase, and phosphorylase activities. Signaling pathways mainly included starch and sucrose metabolism, as well as photosynthesis. Additionally, some differentially expressed genes were verified by fluorescence analysis. The results showed that knockout of OsCIPK17 affected photosynthesis and starch-, sucrose-, and amino acid metabolism-related gene expression; furthermore, the mutation reduced PSII utilization efficiency, it blocked the synthesis and metabolism of starch and sucrose, and affected the formation and transport of assimilates, thereby reducing final grain weight.